PENERAPAN LEARNING MANAGEMENT SYSTEM MELALUI MODUL DIGITAL, WORKSHOP, DAN PENDAMPINGAN DI MASA PANDEMI COVID-19 - Berri Brilliant Albar (LPPM Universitas Andalas, 2020)
Higher education institutions need to prepare online learning in response to the challenges of the needs of the industrial revolution 4.0. In addition, external problems will increase in 2020, one of which is the emergence of the corona virus which has become a pandemic. The pandemic situation forces universities to immediately adapt in learning activities. The Decree of the Minister of Education and Culture is to continue the implementation of distance education online for an indefinite time limit. This situation raises several problems in universities, including the readiness of human resources, facilities, and others. Over time, lectures have started, so this problem must be resolved immediately in order to achieve learning goals and improve the quality of education in tertiary institutions in times of crisis like today. Increasing mastery of LMS by lecturers and providing modules and standardizing aesthetics are one of the efforts of education providers to deliver quality services (reliability, assurance, tangible, empathy, and responsiveness) and satisfying service recipients (community/students). This activity succeeded in conducting efficient and effective technical workshops and modules to increase understanding of LMS mastery in a short time.